1968
DOI: 10.1172/jci105930
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of DNA synthesis in fat cells and stromal elements from rat adipose tissue

Abstract: A B S T R A C T The incorporation of tritiated thymidine into the deoxyribonucleic acid (DNA) of adipose fat and stromal cells was followed under a variety of conditions. After in vitro incubation of adipose slices or up to 2 days after in vivo injection of the isotope, all DNA radioactivity was in the stromal cell fraction. From 2 to 15 days after thymidine injection total tissue DNA radioactivity was constant, while between 2 and 5 days after injection label in fat cell DNA increased markedly. Thus new label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

1971
1971
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(59 citation statements)
references
References 14 publications
4
55
0
Order By: Relevance
“…The apparent reduction in cell number was found only in those individuals with extremely small cells. Similarly, it is possible that precursors of adipose cells containing little lipid may exist in the adipose depot and thus not be measured by the present techniques (15). If forced feeding induced the formation of substantial numbers of these precursor cells, an increase in cell number would go undetected.…”
Section: Adipose Cell Numbermentioning
confidence: 89%
“…The apparent reduction in cell number was found only in those individuals with extremely small cells. Similarly, it is possible that precursors of adipose cells containing little lipid may exist in the adipose depot and thus not be measured by the present techniques (15). If forced feeding induced the formation of substantial numbers of these precursor cells, an increase in cell number would go undetected.…”
Section: Adipose Cell Numbermentioning
confidence: 89%
“…Subsequent studies confi rmed the existence of a mitotically active cell population in WAT ( 7 ), and that WAT expansion is associated with increases in total DNA content and adipocyte number ( 26 ). Following the development of methods for separating WAT into adipocyte and stromal vascular fractions (SVFs) ( 27 ), the source of these new adipocytes was determined by Hollenberg and Vost ( 28 ): using tritiated thymidine to monitor DNA synthesis in WAT, they detected temporal progression of radioactivity from the SVF to mature adipocytes, thereby inferring the presence of an adipocyte precursor cell in the SVF ( 28 ). Shortly thereafter, studies reported growth of fi broblast-like cells from the SVF that are capable of adipogenesis (29)(30)(31).…”
Section: Adipose Tissue Enters the World Of Multipotent Stem Cellsmentioning
confidence: 99%
“…Tissue dissociation studies have implicated the adipose stromal vascular fraction (SVF) as a possible site of origin for adipose stem cells. The SVF is a heterogeneous mixture of cells that can be isolated from adipose tissue after dissociation and centrifugation, in which adipocytes float and the remaining cells pellet (Hollenberg and Vost, 1968). The SVF is composed of a myriad of cells, which includes fibroblasts, endothelial cells, hematopoietic cells and neural cells.…”
Section: Identifying and Characterizing Adipose Stem Cellsmentioning
confidence: 99%
“…In the 1960s, it was shown in rodents that cells within adipose depots proliferate, that adipocytes are renewed and that adipocytes have a finite lifespan (Hellman and Hellerstrom, 1961;Hollenberg and Vost, 1968). Indeed, caloric excess stimulates the adipose stem cell compartment to proliferate and differentiate.…”
Section: Reviewmentioning
confidence: 99%